Hamstring injury in a rink hockey player. Does sport practice influences in injuries prognosis? - Bernat de Pablo; Gil Rodas; Martí Casals (Apunts Sports Medicine)
We describe the case of a young rink hockey player who sustained a hamstring injury, a transversal rupture of the biceps femoris proximal tendon with retraction of the distal portion while playing. Despite a surgical approach is usually recommended in elite athletes from other sports with this kind of injuries, the biomechanics of the sport must be taken into consideration when the treatment is decided.